Pengaruh Buzzer Marketing, Influencer Marketing, dan Brand Trust Terhadap Purchase Intention pada Produk Wardah di TikTok Shop pada Mahasiwa Prodi Manajemen Universitas 17 Agustus 1945 Surabaya: Buzzer Marketing, Inflencer Marketing, Brand Trust, Purchase Intention - Ainiya, Khurrotun Ainiya; Estik Hari Prastiwi (Widya Balina, 2026)
The following study aims to analyze the influence of buzzer marketing, influencer marketing, and brand trust on purchase intention of Wardah products on TikTok Shop. The background of the study is based on the increasing use of TikTok Shop as a social commerce platform and the importance of digital marketing strategies in influencing consumer purchasing intention, especially in the cosmetics industry that demands brand trust. The research method uses a quantitative approach with a questionnaire distributed to 100 respondents. Data were analyzed through validity and reliability tests, classical assumption tests, and multiple linear regression. The results indicate that all instruments are valid and reliable and the model meets classical assumptions. Partially, buzzer marketing, influencer marketing, and brand trust have a significant effect on purchase intention, with coefficients of 0.494, 0.362, and 0.264, respectively. Simultaneously, all three variables also have a significant effect. The coefficient of determination value of 0.535 indicates that the variation in purchase intention is explained by these three variables.